Impact of Lanthanum on positive-bias temperature instability - insight from first-principles simulation - Gu, Chen Jie (2014)
The impact of lanthanum (La) on positive-bias temperature instability (PBTI) is examined via first-principles simulation of the electronic properties of the oxygen vacancy (VO) and vacancy-interstitial (VO-Oi) paired defects in the hafnium dioxide (HfO2) gate dielectric. The purpose is to understand the recently reported retardation of PBTI recovery in La-doped HfO2 gate n-MOSFETs, indicating that La doping has made part of the stress induced electron trapping become more permanent. Simulation results show that the formation energy of both defects are significantly decreased by La doping, implying that these defects are more readily formed in the La-doped HfO2 as compared to the undoped counterpart. The higher density of VO’s should increase PBTI effect, contrary to the experimental observation of a reduced PBTI effect. The discrepancy may be reconciled by the smaller gate current in the La-doped n-MOSFET, believed to be due to the larger tunneling barrier that results from La dipoles at the HfO2/SiOx interface. With a smaller gate current, electron trapping – the main mechanism of PBTI – is correspondingly reduced. But the trap state of VO in the La-doped HfO2 remains as shallow as that in the undoped counterpart and could not account for the reduction in the PBTI recovery observed experimentally. On the other hand, the trap state of the VO-Oi defect is found to be much deeper, and the greater ease of its formation in the La-doped HfO2 could explain the reduced PBTI recovery observed experimentally.